Revision of the American genus Platyvelia Polhemus & Polhemus, 1993 (Heteroptera: Gerromorpha: Veliidae) - Rodrigues, Higor D. D.; Burguez Floriano, Carla Fernanda [UNESP]; Zettel, Herbert; Figueiredo Moreira, Felipe Ferraz (Soc Brasileira Entomologia, 2021)
The subfamily Veliinae (Heteroptera: Gerromorpha: Veliidae) includes ten genera worldwide, seven of which are endemic to the American continent. Here, we provide a revision of Platyvelia Polhemus and Polhemus, 1993, which is distributed from the United States to northern Argentina, and included nine valid species prior to this study. Six species are redescribed, the synonymies of P. egregia (Drake and Harris, 1935) and P. verdica (Drake, 1951) with P. brachialis (Stal, 1860) are proposed, a lectotype is designated for P. annulipes, and two species groups are erected based on male characters: the P. annulipes group and the P. brachialis group. Keys to the species groups and species within each group, photos, and distribution maps are also included.
Keywords: Hemiptera; Redescriptions; Semiaquatic bugs; Synonyms; Taxonomy